2010
DOI: 10.1002/chem.201000507
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Reactivity of [Ge9]4− towards [Fe(cot)(CO)3]: Synthesis and Characterization of [Ge8Fe(CO)3]3− and of the Anionic Organometallic Species [Fe(cot)(CO)3]

Abstract: Reaction of cyclooctatetraene (COT) iron(II) tricarbonyl, [Fe(cot)(CO)(3)], with one equivalent of K(4)Ge(9) in ethylenediamine (en) yielded the cluster anion [Ge(8)Fe(CO)(3)](3-) which was crystallographically-characterized as a [K(2,2,2-crypt)](+) salt in [K(2,2,2-crypt)](3)[Ge(8)Fe(CO)(3)]. The chemically-reduced organometallic species [Fe(η(3)-C(8)H(8))(CO)(3)](-) was also isolated as a side-product from this reaction as [K(2,2,2-crypt)][Fe(η(3)-C(8)H(8))(CO)(3)]. Both species were further characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 78 publications
2
19
0
3
Order By: Relevance
“…A study on the reactivity of Ge 9 clusters towards the complex [Fe(cot)(CO) 3 ] (cot=cyclooctatetraene) has shown that, in addition to the formation of [Ge 8 Fe(CO) 3 ] 3− , the reduction of Fe atoms occurs with the formation of [Fe(η 3 ‐C 8 H 8 )(CO) 3 ] − 24. In other cases, such as the synthesis of the organically functionalized cluster anion [PhGe 9 SbPh 2 ] 2− ,25 the reduction of SbPh 3 to intermediate species such as SbPh 2 − and Ph − has been postulated, but the Ph − anions could only be characterized indirectly through the formation of benzene by 1 H NMR spectroscopy 25…”
Section: Introductionmentioning
confidence: 99%
“…A study on the reactivity of Ge 9 clusters towards the complex [Fe(cot)(CO) 3 ] (cot=cyclooctatetraene) has shown that, in addition to the formation of [Ge 8 Fe(CO) 3 ] 3− , the reduction of Fe atoms occurs with the formation of [Fe(η 3 ‐C 8 H 8 )(CO) 3 ] − 24. In other cases, such as the synthesis of the organically functionalized cluster anion [PhGe 9 SbPh 2 ] 2− ,25 the reduction of SbPh 3 to intermediate species such as SbPh 2 − and Ph − has been postulated, but the Ph − anions could only be characterized indirectly through the formation of benzene by 1 H NMR spectroscopy 25…”
Section: Introductionmentioning
confidence: 99%
“…Es ist jedoch bemerkenswert, dass trotz übereinstimmender Elektronenzahl die Struktur und damit die Bindungssituation etwas von der für nido-artige Cluster typischen C 4v -Symmetrie abweicht. [24] Alle bekannten verwandten Cluster,i nd enen Übergangsmetallkomplexfragmente zu einem Wade-Mingos-Cluster beitragen, sind closo-artige Käfige,z .B. Eine Te ndenz zur Bindungslängen-Alternanz lässt sich, wenngleich in geringerem Ausmaß, auch füra lle übrigen Bindungen im Cluster erkennen.…”
Section: Methodsunclassified
“…Im Gegensatz dazu liefert — ebenfalls im Zuge einer Redoxreaktion — die Umsetzung von [Ge9]4— mit [Fe(cot)(CO)3] (cot=1,3,5,7‐Cyclooctatetraen) die paramagnetischen Anionen [Ge8{Fe(CO)3}]3— sowie [Fe(cot(CO)3]—. Entsprechend der Isolobalbeziehung zwischen einer Fe(CO)3‐Einheit und einem Ge‐Zentrum lässt sich der [Ge8{Fe(CO)3}]3—‐Cluster daher direkt von der bereits bekannten, ebenfalls paramagnetischen [Ge9]3—‐Spezies ableiten 1_82. Ebenso unter Umlagerung der zugrunde liegenden Ausgangsverbindung entsteht durch Umsetzung von [Ge9]4— mit Mn2(CO)10 der Komplex [Ge10Mn(CO)4]3—, bei dem das [Mn(CO)4]—‐Fragment an eine Spitze des bislang schwer fassbaren closo‐Zintl‐Ions [Ge10]2— koordiniert ist 1_83…”
Section: Cluster Und Käfigstrukturenunclassified